A teoria histórico-cultural e processo de apropriação da linguagem escrita: repercussões teórico-metodológicas para o fazer docente na Educação Infantil - ABREU NETO, Raimundo Simas (2023)
We conducted this research based on the following problematizing question: from the Historical-Cultural Theory, what theoretical and methodological assumptions can contribute to the practice of teachers in the final stage of Early Childhood Education regarding pedagogical work with Written Language? The overall objective, therefore, was to understand, from the Historical-Cultural Theory, the theoretical and methodological assumptions that contribute to the practice of teachers in the final stage of Early Childhood Education in relation to pedagogical work with written language, with a view to the development of the Didactic Guidelines Handbook. We defined specific objectives as follows: a) Situate the conceptions of the child and their learning and development process in Early Childhood Education based on the Historical- Cultural perspective; b) Identify the conceptions of the collaborating teachers in the research about children and their learning and development process, language, written language, and the appropriation process in Early Childhood Education; c) Investigate which activities related to written language are prioritized in learning situations and whether they have favored the construction of foundations for its appropriation; d) Develop theoretical and methodological guidelines, materializing them in the Didactic Guidelines Handbook, to support practices involving written language in the final stage of Early Childhood Education at CEI Aquarela, in the municipality of Alto Alegre do Pindaré – MA. To achieve the research objectives, we chose a qualitative research approach and collaborative action research methodology (DESGAGNÉ, 2007; IBIAPINA, 2008). Data generation occurred through the use of narrative interviews, document analysis, and reflective sessions. The research collaborators were two Pre- K II teachers and the Pedagogical Coordinator of the Aquarela Early Childhood Education Center, a school located in the municipality of Alto Alegre do Pindaré – MA. We adopted as theoretical references the assumptions of the Historical-Cultural Theory, based on the theorizations of Vygotsky (1988; 1995; 2000; 2007; 2010); Luria (1988; 2001); Leontiev (1978; 1988); Mello (2004; 2005; 2010), Bakhtin/Volochínov (2006); Geraldi (2000), among others, used in data analysis and reflective sessions. The results point to the need to establish training spaces that encompass aspects related to the appropriation process of written language in Early Childhood Education, in order to broaden the perspective of teachers on certain concepts, which at times diverged from the assumptions assumed in this research. Based on this finding, as a result of collaborative work, we propose a handbook of theoretical and methodological guidelines to support Early Childhood Education teachers in the organization of learning situations.